ANALISIS IRIO 2016 TENTANG PERDAGANGAN SUMATERA UTARA-ACEH TERHADAP PERTUMBUHAN EKONOMI ACEH - nuri rosmika rosmika; jufrizal jufrizal jufrizal (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2022)
This study aims to analyze the impact of Aceh's trade with North Sumatra Province on economic growth in Aceh using the 2016 IRIO model. As a result, the dependence of North Sumatra's output on inputs from Aceh is greater than the dependence of Aceh's output on inputs from North Sumatra. From the simulation results on investment in the food crop agriculture sector and the plantation sector, it is also seen that the economic growth of North Sumatra will be more profitable. This should be the basis for future economic development in Aceh. This research is only in the form of an impact analysis, the analysis of the influence can be considered for further research.